Responses of taro plant (Colocasia esculenta L. Schott) to cormel size as planting material, NPK application and aphid infestation - Lakitan, B.; Ria, R. P.; Putri, H. H.; Achadi, T.; Herlinda, S. (International Journal of Agricultural Technology, 2021)
The strong correlation amongst pairs of cormel morphological traits was found between cormel weight with diameter (r = 0.9068) and with length (r = 0.8659). Thus, cormel weight was used as main indicator of cormel size. Taro plant consists of one mother plant and many suckers. Cormel weight consistently exhibited positive effects on number of suckers and base diameter, length and width of the largest leaf, length and diameter of petiole measured consecutively at 3 WAP, 5 WAP, and 7 WAP. However, Increased in number of suckers did not affect growth of mother plant as indicated by constant number and size of leaves produced by the mother plant. Response of taro plant to NPK application was monitored every 2 days based on SPAD value. If the NPK was applied at 4 WAP, during early vegetative phase, it took 12 days before SPAD value dropped back to pretreated condition but if it was applied at 12 DAP, during tuber development phase, it only needed 6 days. This finding suggests that more frequent NPK application is needed by taro plant for enhancing tuber growth. Aphids can seriously damage the taro plant. Aphids attacked leaves at all dimensions, but serious damage (score = 4) mostly observed in older leaves. Cormel size positively affects growth traits yet did not affect number of leaves and leaf water content. It is recommended for farmers to use larger cormel size for taro cultivation